Construction and validation of data collection instrument content in a neonatal intensive care unit - Natalie Dantas Costa Lima; Viviane Martins da Silva; Beatriz Amorim Beltrão (Rev Rene)
To allow systematic data collection, the study aimed to construct and validate a clinical evaluation instrument for neonates hospitalized in the Intensive Care Unit. A methodological study was conducted from January to June 2008, which was organized into two steps: bibliographical search for subsidizing the construction of the instrument and appropriateness of content by experts from the State of Ceará. The instrument was composed of ten sections: personal data of the mother and the newborn, vital signs, physical/skin integrity, head/neck, nervous system, respiratory system, cardiovascular system, gastrointestinal system, urogenital system, and mother-child binomial. Relevant nursing diagnoses to each section were included. All the sections were considered by the experts to be adequate. Four sections received the maximum score of agreement: mother and newborn personal data, head/neck, cardiovascular system and genitourinary system. It is believed that the implementation of this instrument can help nurses to identify indicators that reflect possible nursing diagnoses.